Pendidikan Islam Moderat di Pondok Pesantren Tanbihul Ghofiliin Banjarnegara - Faozi, Irfan; Mubin, Nurul; Fuadi, Salis Irvan (Kartika: Jurnal Studi Keislaman, 2024)
This study aims to explore the practice of moderate Islamic education in pesantren. The research method used is descriptive qualitative. The primary data sources come from interviews with the Kiai, the head of pesantren, the education section, and the board of supervisors of the pesantren management. This study's results indicate that moderate Islamic education in Islamic boarding schools refers to the teachings of Ahlussunnah wal Jama'ah. The practice begins with the planning stage of activities and learning. This planning is the basis for moderate Islamic education by learning yellow books (kitab kuning) and various educational activities and cultures. In these activities, the values ​​and insights of Islamic moderation are internalized through insertion patterns. Pesantren has also collaborated with various parties outside the pesantren in socializing insights oriented towards moderate Islam. The experts presented are Ahlussunnah wal Jama'ah scholars who have moderate views.